2021
DOI: 10.1038/s41598-021-99484-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, causes and consequences of moderate and severe traumatic brain injury as determined by Abbreviated Injury Score in the Netherlands

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability. Epidemiology seems to be changing. TBIs are increasingly caused by falls amongst elderly, whilst we see less polytrauma due to road traffic accidents (RTA). Data on epidemiology is essential to target prevention strategies. A nationwide retrospective cohort study was conducted. The Dutch National Trauma Database was used to identify all patients over 17 years old who were admitted to a hospital with moderate and severe TBI (AIS ≥ 3) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
5
11
2
2
Order By: Relevance
“…In this study detailed data on TCSI showed that C2 was the most common location of cervical spine fracture, followed by C6-C7. This is in line with other studies [1,4,21]. More than half the patients suffered from complete spinal cord injury with C3-C4 being the most common location for the spinal cord injury.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study detailed data on TCSI showed that C2 was the most common location of cervical spine fracture, followed by C6-C7. This is in line with other studies [1,4,21]. More than half the patients suffered from complete spinal cord injury with C3-C4 being the most common location for the spinal cord injury.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, 9% of patients with severe TCSI had associated severe TBI. The incidence of TCSI and its association with TBI is in accordance with several other reports from literature [1][2][3][4][7][8][9][10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Lastly, polytrauma is common in patients with TBI. 26 Rehabilitation medicine consultants train to manage all injuries (for example, spinal cord injury or complex orthopaedic and musculoskeletal injuries) and any co-existing conditions. Early rehabilitation input is associated with reduced length of stay and other benefits and later the same expert can, for example, support return to work.…”
Section: The Underlying Problemsmentioning
confidence: 99%